Peran Guru IPA dalam Pemanfaatan Media Pembelajaran Interaktif - EL Basthoh; Novyta Novyta (Kappa Journal, 2020)
Inetractive learning media is a medium that can help students and teachers in learning.This study aims to see the role of science teachers in the use of instructional media. This type of research is qualitative non-experimental. The population of this study were students of SMPN 2 Singai Aur Pasaman Barat. Sampling using purposive sampling. Data were collected through a questionnaire with 2 indicators. Based on data analysis using statistical data in the form of percentages and relative frequencies, it was found that the indicator of teacher control of the media used had a score of 94.61% and the media indicators used were good, efficient, and could attract the attention of students in the learning process 88.31%so that it could be concluded that the role of science teachers in the use of interactive learning media has a score of 91.46% with a good category.DOI: 10.29408/kpj.v4i2.2838